Governmental Governance of Megaprojects: The Case of EXPO 2010 Shanghai. Issue 1 (February 2017) - Zhai, Zhao; Ahola, Tuomas; Le, Yun; Xie, Jianxun
While the governance of Western megaprojects is indirectly influenced by governments through legislation and regulations, the Chinese state actively oversees and controls projects of societal importance. To provide clarity on the role of the state in Chinese megaprojects, we carried out a case study focusing on EXPO 2010 Shanghai. Our analysis revealed that through a project-specific organization Construction Headquarter (CHQ), the Chinese state executes administrative strength, forces authorities to temporarily integrate their processes for the benefit of the project, influences contractor and resource selection decisions, induces leadership accountability, and promotes shared project values.